Predator recovery, shifting baselines, and the adaptive management challenges they create. Issue 2 (12th February 2019) - Cammen, Kristina M.; Rasher, Douglas B.; Steneck, Robert S.
Abstract: Recent species recoveries following historical depletion have been widely celebrated as conservation success stories. However, the recovery of highly interactive species, particularly predators, generates new management challenges that arise from their potential for wide‐ranging effects on local ecosystems and their poorly understood ecology. In marine systems, many pinniped species share parallel histories of depletion, recovery, and human conflict. Recovering from post‐exploitation populations of small size, these pinnipeds have returned to their present abundance from a largely absent, or severely reduced, recent role in many coastal ecosystems. To address the challenges arising today from real or perceived overabundance of protected pinniped species, we evaluate the prehistorical, historical, and contemporary abundances of six pinniped species that breed in the contiguous United States. This review highlights gaps in current knowledge that limit the implementation of ecologically grounded approaches to adaptive management of protected species in a time of shifting, or lifting, baselines. To address these gaps will require a diverse cadre of natural and social scientists as well as stakeholders to tackle the questions of how we define recovery at a species or ecosystem level, and when we have reached this point, how we move forward in a way that does not repeat a history of depletion, conservation, and recovery. Doing so will require an understanding of what role highly interactive species play in their ecosystems and how this role shifts with changes in ecological context, as well as the sociological and economic impacts of species restoration to humans. This knowledge is integral to the ongoing transition from a focus on preventing species extinction to new, and often unanticipated, challenges arising from the functional implications of species recovery.